2019
DOI: 10.1111/jdv.15360
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis validation and clinical characterization of atopic dermatitis in Nurses’ Health Study 2

Abstract: Background Epidemiologic studies of atopic dermatitis (AD) are often limited by case definitions that have not been validated. Objective In this study, we assessed the accuracy of self‐report of AD in a large cohort of US female nurses, the Nurses’ Health Study 2 (NHS2). We also provide clinical characteristics of AD in the cohort. Methods We sent an electronic questionnaire to NHS2 participants who previously reported ever having a diagnosis of AD. This questionnaire was designed to confirm cases of AD using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…In this study, the rate of AD patients who also had sleep disturbance was 49.2%, which was significantly higher than that of the no AD group (37.7%). The study that analyzed AD cases from the NHS2 in the United States reported that the proportion of nurses who experienced sleep disturbance when AD symptoms were the worst was 40% [23]. Although a direct comparison is difficult, since this study did not investigate the degree of AD symptoms, the fact that about half of nurses in Korea and the United States experience sleep disturbance implies that the healthcare of nurses with AD should address sleep problems.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…In this study, the rate of AD patients who also had sleep disturbance was 49.2%, which was significantly higher than that of the no AD group (37.7%). The study that analyzed AD cases from the NHS2 in the United States reported that the proportion of nurses who experienced sleep disturbance when AD symptoms were the worst was 40% [23]. Although a direct comparison is difficult, since this study did not investigate the degree of AD symptoms, the fact that about half of nurses in Korea and the United States experience sleep disturbance implies that the healthcare of nurses with AD should address sleep problems.…”
Section: Discussionmentioning
confidence: 91%
“…It is meaningful to examine the prevalence of AD among nurses, since the prevalence of AD differs according to occupation [30] and having AD is known to affect presenteeism, overall work impairment, and activity impairment [31]. A previous study that analyzed NHS2 data reported that 57% of nurses with AD were diagnosed with it as an adult [23], suggesting that the cause of such a high prevalence of AD among nurses is the nursing job. However, this study did not include the exact time of diagnosis of AD, making it difficult to identify whether the high prevalence of AD among nurses was related to the work shift of the nurse.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, patients with allergies have impaired secretion of innate interferons which can increase their risk of developing respiratory viral infections [ 18 ]. Our data are limited as details regarding type of allergy or allergic condition are not available, although reliability of self-reported allergic conditions has been previously established in other cohorts [ 20 ]. We were able to adjust for self-reported asthma in our models, evaluating physical and mental health symptoms to adjust for the potential confounding effects of a comorbid asthmatic condition.…”
Section: Discussionmentioning
confidence: 99%